PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. AGUNG TOYOTA CABANG SOEKARNO HATTA DI PEKANBARU - Dewi, Diana Sri (Sekolah Tinggi Ilmu Ekonomi Riau, 2017)
This study aims to determine the effect of Work Environment on Employee Performance At PT Agung Toyota Cabang Soekarno Hatta In Pekanbaru. As for the population in this study are all employees in PT Agung Toyota Cabang Soekarno Hatta In Pekanbaru, which amounted to 44 people and the population in this study used as a sample by using the census method of all employees. Data analysis used is descriptive analysis, beside that also use analysis of quantitative analysis that is using simple linier regression with help of program SPSS version 17.00. From the results can be concluded a simple linear regression analysis that the work environment has a significant effect on employee performance at PT Agung Toyota Cabang Soekarno Hatta In Pekanbaru. The result of simple linear regression analysis is Y = 6,730 + 0,857X + e